سياسات وبرامج البنك المركزي وأثرها على حجم التمويل المصرفي: دراسة حالة المصارف السودانية خلال الفترة 1997-2017 - اد: إبراهيم فضل المولى; أ. مصطفى ابراهيم عبد النبي (White Nile Journal for Studies and Research, 2020)
The study aimed to measure the effect of some policies and programs of the Central Bank on the volume of bank financing. The problem of the study was to know the extent of the influence of the policies and programs of the Central Bank of Sudan on the performance of Sudanese banks. Murabaha and the volume of bank financing provided by the Sudanese banking system. After analyzing the study data using the Eviews-9 statistical package, the study had reached at set of results, the most important of which are; the increase in the statutory cash reserve ratio leads to a decrease in the volume of bank financing, with a significant impact of the central bank's policies related to determining the profit margin with inverse relation to the volume of bank financing, which affects the profitability of banks. especially as they mainly rely on bank financing. The study was concluded by recommending the provisions of coordination between the Central Bank of Sudan and the operating banks when setting policies so that complete harmony occurs when the policies are implemented. This action leads to raising the efficiency of the banks' performance. In addition the necessity for the Central Bank to develop flexible policies that would be in line with any changes that may occur in the economic indicators in macroeconomic activity in general and banking activity in particular, as well as with any developments that the global economy may be exposed to it.